2019
DOI: 10.1002/bab.1823
|View full text |Cite
|
Sign up to set email alerts
|

Engineering microalgae through chloroplast transformation to produce high‐value industrial products

Abstract: The last few years have seen an ever‐increasing interest in the exploitation of microalgae as an alternative platform to produce high‐value products such as biofuels, industrial enzymes, therapeutic proteins, including antibodies, hormones, and vaccines. Due to some unique attractive features, engineering of the chloroplast genome provides a promising platform for the production of high‐value targets because it allows manipulation of metabolic processes in ways that would be impossible, or at least prohibitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 78 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…Microalgal genetic engineering technologies have been fully established only for Chlamydomonas reinhardtii ( Young & Purton, 2016 ). Although other microalgal strains have been successfully transformed, these are usually one-time cases with low reproducibility ( Siddiqui et al, 2019 ). In addition, native isolates are well adapted to local conditions and exhibit better performance and robustness ( Alishah Aratboni et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgal genetic engineering technologies have been fully established only for Chlamydomonas reinhardtii ( Young & Purton, 2016 ). Although other microalgal strains have been successfully transformed, these are usually one-time cases with low reproducibility ( Siddiqui et al, 2019 ). In addition, native isolates are well adapted to local conditions and exhibit better performance and robustness ( Alishah Aratboni et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the inherent features of algae such as lack of infectious agents or toxins, efficient folding of complex proteins and scope for the development of whole algae as low-cost oral vaccine, makes them ideal platform for heterologous production and offer several advantages over the better established microbial and mammalian systems. Although, most of the chloroplast transformation attempts have been made in the model microalgae Chlamydomonas , the successful chloroplast engineering has also been demonstrated in few other microalgal species [reviewed by Siddiqui et al ( 2020 )]. It was reported that over 100 different recombinant proteins have been successfully expressed in algal chloroplast.…”
Section: Case Studies For Genetic Engineering In Microalgaementioning
confidence: 99%
“…An additional advantage for algae cultures corresponds to the lack of competition for agricultural land; making them a sustainable approach as excellent “cellular factories” to produce high-value compounds [ 19 ], while reducing the carbon dioxide levels generated by anthropogenic//human activities [ 20 ]. Microalgae strains are commonly grown for the production of functional foods and aquaculture products given their contents of functional and nutritional compounds [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%